Possible Involvement of Opioidergic and Serotonergic Mechanisms in Antinociceptive Effect of Paroxetine in Acute Pain - Erdem N. Duman; Murat Kesim; Mine Kadioglu; Ersin Yaris; Nuri Ihsan Kalyoncu; Nesrin Erciyes (Elsevier, 2004)
Antidepressant drugs, especially tricyclics have been widely used in the treatment of chronic pain, but not in acute pain. Because of numerous undesirable side effects, the selective serotonin reuptake inhibitors (SSRIs), with their favorable side effect profile, are preferred nowadays. An activation of the endogenous opioid mechanisms or potentiation of the analgesic effect mediated by serotonergic and/or noradrenergic pathways are thought to be involved in the antinociceptive action of SSRIs. In this study, the potential antinociceptive effect of paroxetine and its interaction with opioidergic system and serotonin receptors were evaluated. The antinociceptive effect of paroxetine was tested using a hot plate test in mice. Paroxetine, a SSRI antidepressant drug, induced an antinociceptive effect following i.p. administration. This antinociception was significantly inhibited by naloxone, an opioid receptor antagonist, suggesting the involvement of opioidergic mechanisms. While ondansetron (a 5-HT3-receptor antagonist) inhibited the effect of paroxetine, ketanserin (a 5-HT2-receptor antagonist) could not. In conclusion, paroxetine-induced antinociception, similar to morphine, suggests an involvement of direct or indirect action (via an increase in release of endogenous opioid peptide(s)) at opioid receptor sites and an involvement of serotonergic mechanisms mainly at the receptor level. Keywords:: paroxetine, nociception, hot plate test